The spatiotemporal evolution of atmospheric boundary layers over a thermally heterogeneous landscape - M. R. Mangan; M. R. Mangan; J. Vilà-Guerau de Arellano; B. J. H. van Stratum; M. Lothon; G. Canut-Rocafort; O. K. Hartogensis (Atmospheric Chemistry and Physics)
We study the diurnal variability in the atmospheric boundary layer (ABL) across spatial scales (between ∼100 m and ∼10 km) of irrigation-driven surface heterogeneity in the semi-arid landscape of the 2021 Land surface Interactions with the Atmosphere over the Iberian Semi-arid Environment (LIAISE) experiment on the northeastern Iberian Peninsula. We combine observational analysis with explicit simulation of the ABL using observationally driven large-eddy simulation (LES) to better understand the physical mechanisms controlling ABL dynamics in heterogeneous regions. Our choice of spatial scales represents current and future single grid cells of global models, demonstrating how the sources and magnitude of subgrid-scale heterogeneity vary with model resolution.